Contact allergy to perfume constituents: isoeugenol and eugenol - Rudzki, Edward; Rebandel, Paweł; Jaworski, Edmund (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2004)
In 2 751 patients with dermatitis 246 persons were positive to perfume mixture (PM). In this group 94 patients agreed to be tested with 8 constituents of PM. Each of this constituents was used in 3 concentrations: 1%, 0.25% and 0.1%. The aim of present paper was the investigation of contact sensitivity to isoeugenol and eugenol. To first of this substances was sensitive 36.17% of persons positive to PM and to second – 18.8%. Contact sensitivity to isoeugenol (compared to eugenol) is not only more frequent but also more strong. In the same patients simultaneous contact sensitivity to both described aromats is frequent. It was observed in 44% patients positive to isoeugenol and in 88% positive to eugenol.